Timing of Delivery in Women With Diabetes: A Population-Based Study. Issue 8 (August 2020) - Metcalfe, Amy; Hutcheon, Jennifer A.; Sabr, Yasser; Lyons, Janet; Burrows, Jason; Donovan, Lois E.; Joseph, K. S.
Abstract : (Abstracted from Acta Obstet Gynecol Scand 2020;99:341–349) Pregestational and gestational diabetes have been associated with an increased risk of neonatal morbidity and mortality, including higher rates of macrosomia, shoulder dystocia, and other birth injuries. While it has been hypothesized that delivery at earlier term gestation may reduce the risk of neonatal complications associated with diabetes in pregnancy, there have been very few studies to examine the timing of delivery among women with diabetes.